Gallstone ileus after laparoscopic cholecystectomy - Ivanov, I (Carol Davila University Press, 2012)
Gallstone ileus represents a rare complication (0,3-0,5%) of a serious, but common disease-gallstones, which affect around 10% of the population in the USA and Western Europe. Associated diseases (usually severe), elderly patients, delayed diagnosis and therapy due to late presentation to the hospital, account for the morbidity and mortality rates described in literature. We present the case of a patient with partial colon obstruction due to a large gallstone that was “lost” during an emergency laparoscopic cholecystectomy. The calculus eroded the intestinal wall, partially occluding the lumen, triggering recurrent Kerwsky-like, subocclusive episodes. The intraperitoneal abscess has spontaneously drained through the subhepatic drain and once the tube has been removed, a persistent intermittent fistula became obvious.